2021
DOI: 10.3389/fbioe.2021.794304
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable Cellulases / Xylanases From Thermophilic and Hyperthermophilic Microorganisms: Current Perspective

Abstract: The bioconversion of lignocellulose into monosaccharides is critical for ensuring the continual manufacturing of biofuels and value-added bioproducts. Enzymatic degradation, which has a high yield, low energy consumption, and enhanced selectivity, could be the most efficient and environmentally friendly technique for converting complex lignocellulose polymers to fermentable monosaccharides, and it is expected to make cellulases and xylanases the most demanded industrial enzymes. The widespread nature of thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 210 publications
0
15
0
Order By: Relevance
“…Therefore, this work has provided an additional improvement in the clari cation of the microbial role in the deconstruction of organic matter and has laid the foundations for setting-up controlled ecosustainable bioconversion reactions. Enzymatic degradation, which has a high yield, low energy consumption, and enhanced selectivity, could be the most e cient and environmentally friendly technique for converting complex lignocellulose polymers to fermentable monosaccharides, and it is expected to make cellulases and xylanases the most demanded industrial enzymes [59].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this work has provided an additional improvement in the clari cation of the microbial role in the deconstruction of organic matter and has laid the foundations for setting-up controlled ecosustainable bioconversion reactions. Enzymatic degradation, which has a high yield, low energy consumption, and enhanced selectivity, could be the most e cient and environmentally friendly technique for converting complex lignocellulose polymers to fermentable monosaccharides, and it is expected to make cellulases and xylanases the most demanded industrial enzymes [59].…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, showed high enzyme activity when compared to uncomplexed cellulases. Improving lignocellulolytic enzyme stability under adverse environmental conditions is also highly sought, as it allows hydrolysis at elevated temperatures, which is often necessary for industrial biomass conversion processes [ 349 ]. Using targeted evolution, a recent study has demonstrated 820-fold increased thermostability in the GH11 family [ 350 ].…”
Section: Recent Advancesmentioning
confidence: 99%
“…Chemical engineering Study on dye-linked L-lactate dehydrogenase [66], lignification [67], dishwashing machine [68], degradation of lignocellulose [69], biodegradable polymer, biotransformation, fine chemical industry, bio-bleaching and dye decolorizing agent [70], renewable bioethanol [71] and enzyme immobilization for the hydrolysis reaction [72]. The most important enzymes: Lipase, cellulase, xylanase, glucosidase and amylase.…”
Section: General Analysismentioning
confidence: 99%